A Model for Applying the Tisikkhā Principles in Improving the Quality of Life of the Elderly in NongYai Subdistrict School for the Elderly, Si Somdet District, Roi Et Province - Phraatikarn Pramaul Athipanyo; Phramaha Mit Thitapanyo; Phra Soponphattanabundit (Dhammathas Academic Journal, 2022)
The objectives of this research were: 1) to study the use of the Tisikkhā principles in improving the quality of life of the elderly; 2) to study the application of the Tisikkhā principles to improve the quality of life of the elderly at NongYai Sub district School for the Elderly, Si Somdet District Roi Et Province; 3) to study the model for applying the Trisikkha principle in improving the quality of life of the elderly at NongYai Sub district School for the Elderly. This study was carried out by means of qualitative research, and the obtained data were interpreted by descriptive analysis. The research results were as follows: 1. The application of the Tisikkhā principles to improve the quality of life for the elderly: physical aspect: the elderly develop self-consciousness and stay in heedfulness; social aspect: the elderly set themselves up within the framework of good social conduct; mental aspect: the elderly have trained their minds to be bright and develop the wisdom to be a reasonable person; intellectual aspect: the elderly have self-development in daily life and live together in society happily according to the Tisikkhā principles. 2. The application of the Tisikkhā principles to improve the quality of life of the elderly at NongYai Sub district School for the Elderly, Si Somdet District Roi Et Province: physical aspect: they have beautiful physical behaviors; mental aspect: they are emotionally in the Dhamma and have the bright mind; intellectual aspect: to create knowledge and understanding of the changes of nature to create a free mind. 3. The model for applying the Trisikkha principle in improving the quality of life of the elderly at NongYai Sub district School for the Elderly: physical aspect: physical behavior is beautiful because there are precepts as the body cover; mental aspect: calm mind, not distracted mind, bright mind to create relaxation because the mind is concentrated; intellectual aspect: contemplation and knowing the emotions, enlightenment according to the Dhamma state because wisdom is the lead.